POSSIBILITIES OF MAIZE HYBRIDS UTILISATION IN CANNED BABY CORN PRODUCTION - Nikolić, Valentina (Journal on Processing and Energy in Agriculture, 2021)
Five maize hybrids were used in this research: two yellow and one white dent, sweet hybrid, and yellow popcorn. Five brine recipes with acetic acid were examined, of which two with the addition of potassium sorbate. The brines with preservatives were stable for 16 months without colour changes of the liquid and corn cobs. The pH of brines ranged from 3.39 to 3.89. Canned hybrids ZP 366 and ZP 611k in brine marked as Number 5 showed the best sensory characteristics. The protein content determined in ZP 366 (9.56 %) and ZP 611k (10.23 %) did not vary significantly compared to whole-grain maize flour, while crude fibre content (7.67 and 6.88 %), and ash content (21.96 and 20.72 %) were significantly higher than in flour (crude fibre: 2.40; 2.64 %, ash:1.35; 1.48%, respectively). This research will be continued in order to implement preliminary findings and new data on this subject.
Keywords: maize hybrids, baby corn, canned vegetables, food production